Outbreak of Clostridium difficile PCR ribotype 027-the recent experience of a regional hospital - Oleastro, M. (2014)
Background: Clostridium difficile infection (CDI) is the leading cause of healthcare-associated diarrhea, and several outbreaks with increased severity and mortality have been reported. In this study we report a C. difficile PCR ribotype 027 outbreak in Portugal, aiming to contribute to a better knowledge of the epidemiology of this agent in Europe. Methods: Outbreak report with retrospective study of medical records and active surveillance data of all inpatients with the diagnosis of CDI, from 1st January to 31th December 2012, in a Portuguese hospital. C. difficile isolates were characterized regarding ribotype, toxin genes and moxifloxin resistance. Outbreak control measures were taken, concerning communication, education, reinforcement of infection control measures, optimization of diagnosis and treatment of CDI, and antibiotic stewardship. Results: Fifty-three inpatients met the case definition of C. difficile-associated infection: 55% males, median age was 78.0 years (interquartile range: 71.0-86.0), 75% had co-morbidities, only 15% had a nonfatal condition, 68% had at least one criteria of severe disease at diagnosis, 89% received prior antibiotherapy, 79% of episodes were nosocomial. CDI rate peak was 13.89/10,000 bed days. Crude mortality rate at 6 months was 64.2% while CDI attributable cause was 11.3%. Worse outcome was related to older age (P = 0.022), severity criteria at diagnosis (leukocytosis (P = 0.008) and renal failure), and presence of fatal underlying condition (P = 0.025). PCR ribotype 027 was identified in 16 of 22 studied samples. Conclusions: This is the first report of a 027-CDI outbreak in Portugal. We emphasize the relevance of the measures taken to control the outbreak and highlight the importance of implementing a close and active surveillance of CDI.